One percent for the kids : new policies, brighter futures for America's children - Sawhill, Isabel V. (Brookings Institution Press, 2003)
This volume argues that the life prospects of children can be improved substantially by reallocating one per cent of the gross domestic product to children's programmes. Each chapter contains a specific proposal for change, as well as information about the rationale and cost of the initiative.